The Impact of Coupling Function on Finite-Time Synchronization Dynamics of Multi-Weighted Complex Networks with Switching Topology. (21st March 2019) - Yang, Bin; Wang, Xin; Fang, Jian-an; Xu, Yuhua
Abstract : This paper is not only concerned with the problem of finite-time synchronization control for a class of nonlinear coupling multi-weighted complex networks (NCMWCNs) with switching topology but also an attempt at using the derived results and Lyapunov stability theory to study the impact of nonlinear coupling function on finite-time synchronization dynamics of the raised network model. Firstly, different from the existing related results, based on the existing and new finite-time theories, two finite-time synchronization controllers are, respectively, designed to make the considered network achieve finite-time synchronization. Secondly, according to the obtained results, several finite-time synchronization dynamics criteria are established to show that nonlinear coupled function and the switching of outer-coupling matrix are how to impact finite-time synchronization dynamics. Finally, two illustrated examples are provided to verify the effectiveness of theoretical results proposed in this paper.